Analisis Kesalahan Pemecahan Masalah Matematis Siswa Pada Materi Tali Busur Lingkaran Berdasarkan Tahapan Polya - Oktaharmila, Izma; Sabrun, Sabrun; Sanapiah, Sanapiah (Media Pendidikan Matematika, 2026)
This study aims to improve students’ mathematical problem-solving abilities and learning activities through the application of the Problem Based Learning (PBL) model on circle material in class XI IPS-5 of SMA Negeri 3 Mataram. This research used Classroom Action Research (CAR) with the Kemmis and McTaggart model which consisted of two cycles, namely planning, action, observation, and reflection. The subjects of this study were 35 students of class XI IPS-5. Data collection techniques used were tests, observations, and documentation. The instruments used were mathematical problem-solving ability tests and student learning activity observation sheets. The results showed that the application of the Problem Based Learning (PBL) model was able to improve students’ mathematical problem-solving abilities. In cycle I, the average score of students reached 81.17 with classical completeness of 74.28%, while in cycle II the average score increased to 88.45 with classical completeness of 91.42%. Student learning activities also increased from the fairly active category in cycle I to the active category in cycle II. The increase occurred because students were actively involved in discussions, problem investigations, presentations, and reflections during the learning process. Thus, the application of the Problem Based Learning (PBL) model can improve mathematical problem-solving abilities and student learning activities on circle material.